1996
DOI: 10.1128/aem.62.4.1458-1460.1996
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic, nitrate-dependent microbial oxidation of ferrous iron

Abstract: Enrichment and pure cultures of nitrate-reducing bacteria were shown to grow anaerobically with ferrous iron as the only electron donor or as the additional electron donor in the presence of acetate. The newly observed bacterial process may significantly contribute to ferric iron formation in the suboxic zone of aquatic sediments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
388
3
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 817 publications
(424 citation statements)
references
References 25 publications
20
388
3
7
Order By: Relevance
“…In marine sediments, bacterial oxidation of ironmonosulfide (FeS) with nitrate as electron acceptor was shown by Schippers and Jørgensen (2002). Pyrite (FeS 2 ), however, seems to be mainly oxidized by abiotic processes, whereas bacteria in marine sediments use dissolved Fe 2+ and reduced sulfur species (Straub et al, 1996;Benz et al, 1998;Schippers and Jørgensen, 2002;Jørgensen and Nelson, 2004). At hydrothermal vents, the main research focus until now has been on microbes inhabiting active vent sites or vent fauna symbionts (reviewed in Sievert and Vetriani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In marine sediments, bacterial oxidation of ironmonosulfide (FeS) with nitrate as electron acceptor was shown by Schippers and Jørgensen (2002). Pyrite (FeS 2 ), however, seems to be mainly oxidized by abiotic processes, whereas bacteria in marine sediments use dissolved Fe 2+ and reduced sulfur species (Straub et al, 1996;Benz et al, 1998;Schippers and Jørgensen, 2002;Jørgensen and Nelson, 2004). At hydrothermal vents, the main research focus until now has been on microbes inhabiting active vent sites or vent fauna symbionts (reviewed in Sievert and Vetriani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These different biotic and abiotic Fe redox reactions cause the precipitation, transformation, and dissolution of different minerals and the biogeochemical Fe cycle is connected to many other elementary cycles, e.g. the carbon, nitrogen, sulfur and phosphorous cycle (Canfield, 1989;Martin et al, 1991;Widdel et al, 1993;Straub et al, 1996;Emerson and Moyer, 1997;Boyd et al, 2007). In nature Fe(II)-oxidizing and Fe(III)-reducing bacteria can be found in close proximity to each other, especially when biogeochemical gradients are steep e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1). In the anoxic sedimentary denitrification zone, nitrate can be utilized as an electron acceptor by many microbial processes, including Fe(II) oxidation (Straub et al, 1996;Hauck et al, 2001), anaerobic ammonium oxidation (anammox) (Thamdrup and Dalsgaard, 2002), organic matter oxidation (Hauck et al, 2001) and potentially even for pyrite oxidation (Bosch et al, 2012). The dissolved nitrogen concentration in the water column of (Upper) Lake Constance at more than 50 m depth has been fairly constant over the past 10 years with a concentration of approximately 70 μM (IGKB, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Deeper within the sediments, where oxygen is depleted, iron can be microbially oxidized and reduced through processes coupled to nitrogen species in the denitrification zone. Nitrate-reducing Fe(II) oxidizers require a source of ferrous iron, nitrate and an organic co-substrate (Straub et al, 1996). Enzymatic nitratereducing Fe(II) oxidation has not yet been conclusively demonstrated and it has been suggested that the oxidation of ferrous iron occurs chemically through the production of nitrite during microbial denitrification (Klueglein and Kappler, 2013).…”
Section: Introductionmentioning
confidence: 99%